INTERCELLULAR COMMUNICATION AND TISSUE GROWTH : I. Cancerous Growth - Loewenstein, Werner R. (The Rockefeller University Press, 1967)
Intercellular communication was examined with intracellular electrical techniques in primary and transplanted rat liver cancers. Normal liver cells communicate rather freely with each other through permeable junctional membranes. Cancer liver cells show no communication at all; their surface membrane is a strong barrier to diffusion all around the cell. Cancer cells induce alterations in membrane permeability in normal liver cells; communication among the latter is markedly reduced when cancer cells grow near them.